GE_GERICHTE P/13399/2024 vom 17. Juni 2024 - GE Cour de justice (2024)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;QUALITÉ POUR AGIR ET RECOURIR;FAUX TÉMOIGNAGE;DIFFAMATION;CALOMNIE;EXCUSABILITÉ | CPP.382.al1; CP.307; CPP.310.al1.leta; CP.173; CP.174; CP.14